THE STATISTICAL ANALYSIS OF LABOR MARKET AND FEMALE LABOR FORCE CHARACTERISTICS IN CENTRAL AND EASTERN EUROPEAN COUNTRIES - Jaba, Elisabeta; Sandu, Christiana; Plopeanu, Aurelian; Robu, Ioan; Istrate, Marinela (Studies and Scientific Researches. Economics Edition, 2017)
In this paper we analyze the characteristics of labor markets and female labor force in the countries from Central and Eastern Europe in order to verify the existence of significant differences in female labor participation rate among the countries that experienced the same political and economic system before 1990. The paper seeks to address the following specific objectives: 1) to identify the variables which are strongly correlated with female labor force participation, objective met using correlation analysis; 2) to define clusters of countries based on the determinants of female participation on the labor market, identified previously, using hierarchical cluster method; 3) to verify if the female labor force participation rate differs significantly among the identified clusters by applying the analysis of variance. The results of this study highlight that, in Central and Eastern Europe, we can identify four clusters of countries that share common characteristics of female labor market and female labor force. The analysis of the variation in female labor force participation rate emphasizes different patterns according to identified groups of countries.